Efek Narasi Cagar Budaya pada Intensi dan Kebanggaan Remaja akan Majapahit dan Indonesia - Ginanjar, Agi (UI Scholars Hub, 2018)
This paper discusses the dissemination of information about cultural heritage to the young generation, particularly about the kingdom of Majapahit whose ancient sites are situated in Trowulan, East Java, Indonesia. In the context of public archaeology, heritage information is no longer communicated to the public in mind-numbing ways; instead, it is presented in such a way as to increase positive attitude and behavior toward the cultural heritage. In the context of marketing communication, the dissemination of information which is in accordance with the consumers’ or visitors’ tastes can no longer be performed by presenting raw facts only, but by presenting the information in the form of underdog or topdog stories or narratives. The objective of the research in this paper is to measure the effects of the dissemination of information about Majapahit cultural heritage by means of narratives on public attitude, intention to visit, and pride. The research applied the 3x1 experiment design to the participants. Our research findings confirm that the dissemination of cultural heritage information in the form of topdog narratives directly improved the participants’ attitude toward and intention to visit Majapahit relics in Trowulan. Additionally, the dissemination of cultural heritage information in the form of topdog narratives also increased the participants’ pride in Indonesia.